Marks' basic medical biochemistry : a clinical approach - Lieberman, Michael; Marks, Allan;Chansky, Matthew (Philadelphia, Pennsylvania : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2009)
A core textbook for medical students taking medical biochemistry, 'Marks' Basic Medical Biochemistry' links biochemical concepts to physiology and pathophysiology, using hypothetical patient vignettes to illustrate core concepts. A best-selling core textbook for medical students taking medical biochemistry, "marks' basic medical biochemistry" links biochemical concepts to physiology and pathophysiology, using hypothetical patient vignettes to illustrate core concepts. Completely updated to include full-color art, expanded clinical notes, and bulleted summaries at the end of each chapter, the revised third edition helps medical students understand the importance of the patient and bridges the gap between biochemistry, physiology, and clinical care.
Sect. 1. Fuel Metabolism -- Sect. 2. Chemical and Biologic Foundations of Biochemistry -- Sect. 3. Gene Expression and the Synthesis of Proteins -- Sect. 4. Fuel Oxidation and the Generation of ATP -- Sect. 5. Carbohydrate Metabolism -- Sect. 6. Lipid Metabolism -- Sect. 7. Nitrogen Metabolism -- Sect. 8. Tissue Metabolism -- Appendix. Answers to Review Questions.
Includes bibliographical references and index.
Keywords: BIOCHEMISTRY